Proximity‐dependent biotinylation identifies a suite of candidate effector proteins from Fusarium graminearum. (8th September 2022) - Miltenburg, Mary G.; Bonner, Christopher; Hepworth, Shelley; Huang, Mei; Rampitsch, Christof; Subramaniam, Rajagopal
SUMMARY: Fusarium graminearum is a fungal pathogen that causes Fusarium head blight in cereal crops. The identification of proteins secreted from pathogens to overcome plant defenses and cause disease, collectively known as effectors, can reveal the etiology of a disease process. Proximity‐dependent biotin identification (BioID) was used to identify potential effector proteins secreted in planta by F. graminearum during the infection of Arabidopsis. Mass spectrometry analysis of streptavidin affinity‐purified proteins revealed over 300 proteins from F. graminearum, of which 62 were candidate effector proteins (CEPs). An independent analysis of secreted proteins from axenic cultures of F. graminearum showed a 42% overlap with CEPs, thereby assuring confidence in the BioID methodology. The analysis also revealed that 19 out of 62 CEPs (approx. 30%) had been previously characterized with virulence function in fungi. The functional characterization of additional CEPs was undertaken through deletion analysis by the CRISPR/Cas9 method, and by overexpression into Triticum aestivum (wheat) leaves by the Ustilago hordei delivery system. Deletion studies of 12 CEPs confirmed the effector function of three previously characterized CEPs and validated the function of another four CEPs on wheat inflorescence or vegetative tissues. Lastly, overexpression in wheat showed that all seven CEPs enhanced resistance against the bacterial pathogen Pseudomonas syringae DC3000. Significance Statement: Towards a better understanding of the Fusarium head blight disease, this study utilizes a proteomic tool called proximity‐dependent biotin identification, or BioID, to identify effector proteins from the pathogen Fusarium graminearum . Identification and characterization of effectors will enable pathologists to monitor the pathogen evolution, and use them as potential new targets for fungicide development as part of the integrated pest management programs.